Land, Law and Politics in Africa: Mediating Conflict and Reshaping the State - Abbink, J; Bruijn, Mirjam de; Hesseling, Gerti (African Dynamics, 2011)
This book offers a series of new studies on the dynamics of political and legal culture as well as of conflict management in contemporary Africa, taking inspiration from and honoring the scholarly contributions and impact of Prof. Gerti Hesseling (1946-2009) in African Studies.